Contribution of Psychology in Classroom Management - Suriani, Nidia; Iskandar; Yamin, Martinis (IHSAN : Jurnal Pendidikan Islam, 2024)
Classroom management is the art of managing the class. The aim of this research is to analyze and describe the contribution of educational psychology in classroom management. The method in this research uses a library research approach. In this study there was no research location, because all data was taken from journals, books and scientific proceedings. The data collection technique in this research uses documentation, with data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results of this research are as follows; Firstly, classroom management is a conscious effort to organize so that teaching and learning activities can run systematically. The basic concept that needs to be observed in classroom management is the placement of individuals, groups, schools and the environmental factors that influence them. The aim of classroom management is to support the the teaching and learning process such as creating order and obeying the rules in the classroom during learning. Second, educational psychology is a branch of psychology in its analysis and research that places more emphasis on issues of growth and development, both physical and mental, which are closely related to educational issues, especially those that influence the learning process and success. Third, the contribution of educational psychology in classroom management is in the form of the ability to manage the class well and contribute to students